Implementasi Program Adiwiyata Di Sekolah (Studi Perilaku Siswa Peduli Lingkungan Kelas IV Di UPT SPF SD Inpres Antang 1 Kota Makassar) - Muktazah Adila; Eka Fitriana HS; Jalal; Satriawati; Jusmawati (Kappa Journal, 2024)
This study aims to determine the reasons why there must be an Adiwiyata program and how the Adiwiyata program is implemented at the UPT SPF SD Inpres Antang 1 Makassar City. The type of research used is descriptive with a qualitative approach. The subjects of the study were fourth grade students at the UPT SPF SD Inpres Antang 1 Makassar City. The data collection techniques used were observation, in-depth interviews, and documentation. The results obtained were that Adiwiyata is very important in schools because the Adiwiyata program makes all school residents aware of the importance of maintaining cleanliness and preserving the environment in schools. Even the school has implemented the Adiwiyata program. Some of the things they have done include routine activities every Saturday, determining the picket schedule in each class, and competitions at the end of each semester such as class cleanliness competitions, waste sorting, and producing a work using used materials.